Possible origin of electronic effects in Rh(I)-catalyzed enantioselective hydrogenation - Wu, Hai-Chen; Abd Hamid, Shafida; Yu, Jin-Quan; Spencer, Jonathan B (American Chemical Society, 2009)
Reducing the electron density of ligands switches the regioselectivity of Rh(I)-catalyzed hydrometalation. A reversal of the sense of chiral induction was also observed when chiral ligands are electronically tuned in the same manner. The combined data provide an alternative rationale for the electronic effects often observed in asymmetric hydrogenation.